(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
The socio-economic environment of the outermost regions of the European Union was severely affected by the COVID-19 crisis. Due to their geographical and historical specificities, the outermost regions were significantly lagging behind the rest of the European Union in terms of economic indicators even in the pre-pandemic period. Expectedly, COVID-19-induced shocks additionally potentiated their development gap. The purpose of this paper is to summarise the multiple impacts of the COVID-19 pandemic in Guadeloupe, French Guiana, Réunion, Martinique, Mayotte, and Saint Martin (France), the Azores and Madeira (Portugal), and the Canary Islands (Spain), and the related legislative responses of the European Union aiming at eliminating adverse effects of the crisis and building more resilient societies. The factual assessment is carried out primarily through the prism of the European Commission’s 2021 Study on the Impact of the COVID-19 Pandemic on the Outermost Regions, which underlines the health, economic and social repercussions of the crisis as well as a recommended set of recovery and resilience-building measures in the outermost regions. The legal analysis focuses on the ongoing codification of the rules and measures regulating the governance of the outermost regions as integral parts of the European Union. Pursuant to Article 349 of the Treaty on the Functioning of the European Union (TFEU), the European Union shall adopt specific measures for laying down the conditions for the development of the outermost regions, such as those in the area of fiscal policy, European Structural and Investment Funds, State-aid, agriculture and fisheries policies, and others. In that regard, the paper looks into the recently adopted regulations facilitating the use of EU funds and particular benefits (e.g. tax exemptions) in the outermost regions. Special emphasis is put on the currently tabled initiatives for an updated regulatory framework enabling the outermost regions to improve and strengthen their overall socio-economic position. That mainly refers to the forthcoming European strategy for the outermost regions, to be adopted in 2022. The respective strategy shall lay the foundations for a new strategic approach of the European Union to shaping a sustainable and resilient future for the outermost regions apt to face the challenges of the 21st century, notably those related to green, digital, and demographic transition.